Identification of single nucleotide polymorphisms in GDF9 gene associated with litter size in Garut sheep - Resti Yuliana Rahmawati; Sumadi Sumadi; Tety Hartatik (Universitas Gadjah Mada, 2019)
The growth differentiation factor 9 (GDF9) gene has been regarded as having major impacts on ovulation rate and litter size in sheep. The aim of this study was to identify the single nucleotide polymorphisms (SNPs) of the GDF9 gene and their association with litter size in Garut sheep. For this purpose, a total of 60 ewes of Garut sheep were included in this study. Based on the sheep GDF9 reference sequences (Genbank Acc. No. AF078545.2), one pair of primers (5’-CTGCTGTTTAACCTGGATCGTG-3 5’-GGAGAGCCATACCGATGTCC-3 as forward and reverse, respectively) was used for PCR amplification. The results revealed that four SNPs (g.54C>T, g.60G>A, g.304G>A, and g.333G>A) were found in Garut sheep by direct sequencing. For SNP g.54C>T, the sheep exhibited the highest frequency of allele C and genotype CC. On the other hand, SNPs g.60G>A, g.304G>A, and g.333G>A showed a higher frequency of allele G than allele A, and the GG genotype was predominant in the population. SNP g.333G>A had a significant effect on litter size (p < 0.05), and ewes with the GG genotype had a higher litter size than those with the GA genotype. Genotype distributions for all identified SNPs were in agreement with Hardy-Weinberg equilibrium. We highlight that SNP g.333G>A may be useful as a genetic marker for litter size in Garut sheep.